Mechanisms of Protective Effects of SGLT2 Inhibitors in Cardiovascular Disease and Renal Dysfunction - Liu, Ban; Wang, Yuliang; Zhang, Yangyang; Yan, Biao (Current Topics in Medicinal Chemistry, 2019)
Type 2 diabetes mellitus is one of the most common forms of the disease worldwide. Hyperglycemia and insulin resistance play key roles in type 2 diabetes mellitus. Renal glucose reabsorption is an essential feature in glycaemic control. Kidneys filter 160 g of glucose daily in healthy subjects under euglycaemic conditions. The expanding epidemic of diabetes leads to a prevalence of diabetes-related cardiovascular disorders, in particular, heart failure and renal dysfunction. Cellular glucose uptake is a fundamental process for homeostasis, growth, and metabolism. In humans, three families of glucose transporters have been identified, including the glucose facilitators GLUTs, the sodium-glucose cotransporter SGLTs, and the recently identified SWEETs. Structures of the major isoforms of all three families were studied. Sodium-glucose cotransporter (SGLT2) provides most of the capacity for renal glucose reabsorption in the early proximal tubule. A number of cardiovascular outcome trials in patients with type 2 diabetes have been studied with SGLT2 inhibitors reducing cardiovascular morbidity and mortality. The current review article summarises these aspects and discusses possible mechanisms with SGLT2 inhibitors in protecting heart failure and renal dysfunction in diabetic patients. Through glucosuria, SGLT2 inhibitors reduce body weight and body fat, and shift substrate utilisation from carbohydrates to lipids and, possibly, ketone bodies. These pleiotropic effects of SGLT2 inhibitors are likely to have contributed to the results of the EMPA-REG OUTCOME trial in which the SGLT2 inhibitor, empagliflozin, slowed down the progression of chronic kidney disease and reduced major adverse cardiovascular events in high-risk individuals with type 2 diabetes. This review discusses the role of SGLT2 in the physiology and pathophysiology of renal glucose reabsorption and outlines the unexpected logic of inhibiting SGLT2 in the diabetic kidney.
Keywords: Type 2 diabetes mellitus